The Contract Of Employment, Knowledge Workers, And The â€œK-Economyâ€ - Syed Ahmah, Sharifah Suhanah (Journal of Malaysian and Comparative Law, 2000)
At the time of writing, the K-economy masterplan is still being prepared. The government hopes that it will be ready by the end of year 2000 so that it might be incorporated under Outline Perspective Plan III which will contain Malaysia's development strategy for year 2001 and beyond.